Los archivos históricos provinciales: Estudio de usuarios aplicado en Jaén - Santaella Ruiz, Rita Dolores (Revista General de Información y Documentación, 2007)
The creation of the Provincial Historical Archives in century XX, organizations that arise to compile the notarial documentation, and the new administrative configuration, through the creation of the independent communities, supposes the establishment of centers in which documents of public faith of century XV with those generated by the delegated Administration coexist. The evaluation of the archives, centers denostados in the cultural policies of the public Administration, demonstrates the utility of these companies for the institution to which they belong and for the promotion of the investigation of a society. Also necessity of safeguard it of performances of Administration public, facilities for recovery and information dissemination which they offer to its technologies and the possibility of having the world like client power, including those towns that do not enjoy the history that has one of the first continents populated and civilized of our world, make of the powerful studies of users tools that inform on these consumers of information and would make possible to open the doors of one of the more elitist cultural centers in this society of the well-being, that has of the cultural levels more democratizados of history. To the thread of the previous arguments, this article takes care of the Provincial Historical Archives and their users through a study of cases in the Provincial Historical File of Jaén into which it inquires like waiting room to the establishment of the profile of his investigators, majority customer of this institution.